Advancing Sustainable Practices in Electronic Customer Relationship Management - Mansour, Ahmad; Al-Ahmed, Hind; Deek, Anan; Alshaketheep, Khaled; Asfour, Bara; Alshurideh, Muhammad (International Review of Management and Marketing, 2024)
This paper examines the role of sustainability in determining organisational development and the manner in which it has become a necessity in conducting business. Thus, this research aims at determining the enhancement of sustainable practices in the e-CRM systems. Thus, using surveys and measuring certain e-CRM possibilities quantitatively, interviews and case analyses as qualitative data gathering, the research offers a systemic understanding of how e-CRM may be utilized to encourage sustainability. The preliminary results also reveal a high concern of the respondents towards the sustainability factor in e-CRM with the mean score of 4.2 and considerable awareness of the benefits like cost advantage measure with the calculated score of 4.5 mean. Companies are moderately challenged when it comes to cost and complexity (mean score 3.8) that restrict the integration of sustainability aspect in e-CRM systems, Nevertheless the implementation and planning of sustainability initiative in e-CRM system is high (current initiatives mean score 3.7, planned initiatives mean score 4.1). The qualitative results and cases reveal the ideas, experiences, examples, and quantifiable results, such as a 25% decrease in the usage of paper in the cases and a 30% decrease in energy use. These findings established that e-CRM strategies can be made sustainable, thereby creating improved communication between firms and their customers, whilst mitigating damages to the environment and supporting the long-term sustainability of organisations.